The Education Decentralilation Policy through Implementation of School-Based Management (SBM) - Fathurohman Fathurohman; Achadi Budi Santosa (Institut Agama Islam Negeri Purwokerto, 2020)
The purpose of this study was to reveal the implementation of decentralization policies through the School Based Management (SBM) program. The research method was carried out with a qualitative approach. The data were collected through direct observation and structured interviews with the principal, teachers and employees. The results showed that the implementation of the education decentralization policy was carried out through; (a) determining structural positions (b) managing school finances, (c) structuring teachers and employees, and (d) determining school planning and programs. All stakeholders are able to work in accordance with predetermined main duties and functions and can synergize with one unit to another.